Theoretical Design Science in Human–Computer Interaction: A Practical Concern? - John M. Carroll (Artifact, 2007)
Abstract Design research, without empirical evaluation, is often looked upon as a poor relation to more obviously experimental work. A common reason to reject design studies submitted for publication concerns their failure to provide an empirical evaluation of the use and effects of an artifact in the laboratory or in more realistic field settings. The authors argue that this scepticism towards pure theoretical design research without empirical results not only hinders scientific progress and scientific efficiency in human–computer interaction research, but also discounts the value of designs conceived and realized in practice. Pure theoretical design research has value because envisioning and implementing a design is a form of theorizing, theory integration, theory refinement, and analytic evaluation. The artifact, in essence, embodies a theory, with analytical value independent of its empirical evaluation. The activities of analysis, design, and construction are common in both academe and in design practice, and represent an underexploited resource for systems design science. In part this limitation might stem from the lack of epistemological grounding for design as a knowledge generating activity, and in part from the lack of a distinct methodological perspective from which to assess theoretical design science. The authors ground their perspective with reference to the philosophy of science and through analysis of a design research exemplar, and suggest a set of criteria for evaluating research products in theoretical design science.